Laporan Kasus: Drug-Induced Gingival Enlargement Akibat Konsumsi Amlodipin - Rinawati Satrio; Endang Yunia Ekawati (Fakultas Kedokteran Gigi Universitas Jember, 2020)
Gingival enlargement due to drug side effects is one of the complaints in the oral cavity in patients with certain conditions. The term gingival deformity which is clinically larger than normal is known as gingival enlargement. One of the etiologies of gingival enlargement is a systemic factor caused by the consumption of certain drugs. Drugs that can cause gingival enlargement are Calcium Channel Blocker (CCB) drugs. Amlodipine consumed by hypertensive patients can trigger enlargement of the gingiva. A 72-year-old woman came to the General Soedirman University Dental and Oral Hospital with complaints of the front gums of her upper jaw and a swollen lower jaw since six months ago. The results of the general examination showed that the patient was suffering from hypertension and was taking 5 mg of amlodipine since one year ago. Intraoral examination revealed gingival enlargement, a mild scale extending to the anterior regions of the maxilla and mandible. The Oral Hygiene Index Simplified (OHI-S) examination score was 2.9 (moderate). The patient's diagnosis was gingival enlargement et causa amlodipin. The management was given to patients is Dental Health Education (DHE) and instructions on how to maintain oral hygiene. The conclusion of this case report is that patients with hypertension who consume amlodipine can trigger gingival enlargement.